Frequency of early postoperative adverse events (AEs) in adult patients undergoing elective neurosurgical intervention at tertiary care center in Pakistan - Chandio, Mansoor (Pak J Med Sci, 2021)
OBJECTIVE: The postoperative period is critical in neurosurgical patients, where the incidence of postoperative AEs is significantly high. Most of events occurs during recovery phase and has got relation to anaesthetic management. The objective of study was to determine frequency of early AEs in elective neurosurgical patients. METHODS: This cross sectional study was conducted at our tertiary care center. The duration of study was one year, from August 2017-July 2018. The data was collected using predesigned proforma. The assessment was done on arrival in recovery room (T1) and then at forty five minutes (T2), twenty-fourth hour (T3) and forty-eighth hour (T4) postoperatively. RESULTS: Total ninety-five patients were included. Overall, five hundred and forty AEs were recorded at T1, T2, T3 and T4. Anaesthesia related events like pain, postoperative sore throat, hoarseness, shivering and hypothermia were the commonest (73%). There was a gradual decline in incidence of these events over period of 48 hours. There was no effect of age, sex, BMI and blood loss on incidence of AEs. CONCLUSIONS: Postoperative pain, PONV and shivering were frequently reported AEs. We did not identify the impact of age, sex, BMI, comorbid or type of surgery in terms of having these events.